STUDI KASUS PROGRAM CSR MITRA DESA MANDIRI PT. VALE INDONESIA, TBK. - Sahding, Rahmania (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
The purpose of this study is to find out the planning, implementation and evaluation of the Mitra Desa Mandiri Program PT. Vale Indonesia, Tbk Sorowako, East Luwu Regency. This study uses a case study research method. This type of research is conducted in a qualitative descriptive manner. Data collection techniques are carried out by observation, in-depth interviews and documentation. There were 6 informants in this study. The results of the study show that PMDM planning at the village level begins with a review of the village and medium-term village development work plans, priority design proposals, budget plans, verification, and proposal determination. Activity planning at the sub-district level begins with a study of proposals between villages in the fields of education, health and the economy within the sub-district that is under the authority of the district, this study starts from the priority proposals for sub-district consultations through deliberation. Activity planning at the district level is coordinative planning, starting from the involvement of sub-district delegates in the SKPD forum to the development planning meetings in the district. In implementing PMDM, the coordination meeting is conducted with a series of activities and operational actions from all agreed plans, in this program the community is the owner of activities that will work directly and conduct deliberations to submit accountability reports from the implementation of activities and use of PMDM funds. This evaluation of PMDM was carried out at a certain time by the community, the regional government and PT. Vale, the evaluation is carried out in two stages, which is done in the middle or at the end of the program year, this is formulated from the specific objectives to be achieved from each type of activity in PMDM.